Was können frühere Arbeitszeitverkürzungen fürdie Debatte um die 32-Stunden-Woche lehren? - Hartmut Seifert (Wirtschaftsdienst, 2023)
– This article asks what lessons can be learned from the introduction of the 35-hour week for the current debate in the steelindustry. In retrospect, it can be shown that a compromise in collective bargaining policy cleared the way from the 40- to the 35-hourweek. A package of shorter and more flexible working hours could also make the 32-hour week possible in the steel industry in a simi-larly cost- and distribution-neutral way, especially as large sections of the workforce there already work less than 35 hours.
Keywords: J22; J52; J81; 330; Arbeitszeitgestaltung; Deutschland; Arbeitszeitgestaltung; Deutschland